Relationship between the change of soil moisture content of different soil layers and maize yield - Dóka, Lajos (Acta Agraria Debreceniensis, 2014)
The development of chernozem soil water management and its relationship with maize yields was studied in a 30-years long-term field experiment with different crop-rotation systems (mono-, bi- and triculture), in three crop years with different natural precipitation: a drought (2007), a wet (2008) and a dry (2009 one. The relevant soil layer was divided to three sub-layers: (0–60 cm, 61–120 cm, 121–200 cm) in which the development of soil moisture content was investigated during the whole vegetation. From the results it can be stated that change of the water stock of the upper soil layer (0–60 cm) was the most intensive. Both the direct effect of natural precipitation and irrigation could be observed in the most obvious way in it. Yield result of maize and the highest water supply deficit values in the vegetation were compared in our work too. According to the results it was revealed that among the three studied crop rotation systems it was the monoculture, the success of production of which depends the most of water supply. The most favourable crop rotation system was the triculture from both the aspect of the yield of produced crops and the favourable soil properties too.